Vernalização artificial em genótipos de morangueiro - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The aim of this work was to evaluate the effect of artificial vernalization on six strawberry genotypes. The experiment was carried out in the experimental area of the Universidade Federal do Pampa - Campus Itaqui. According to KÖPPEN, the climate is classified as subtropical with no defined dry season, and the soil is classified as Plintossolo Argilúvico Distrófico. The design used was randomized blocks in a 6x2 bifactorial design with four replications, six strawberry genotypes (CAV 1, CAV 2, CAV 4, CAV 6, CAV 7 and CAV 8) and two types of seedlings (with vernalization and without vernalization). The seedlings were provided by the Santa Catarina State University (Udesc). Five plants were used per plot, with a spacing of 0.25m between rows and 0.25m between seedlings. The crop was planted according to the soil analysis of the area and the recommendations of the Fertilizing and Liming Manual, with 270 kg ha-¹ of N, 250 kg ha-¹ of P₂O₅ and 150 kg ha-¹ of K₂O. To determine the phenological variables, the number of leaves was counted every three days to determine the phyllochronous variable, using the accumulated thermal sum. To assess flowering, the dates of anthesis, start of flowering, full flowering and start of harvest were recorded. To assess production, the fruit was harvested to determine the number and mass of commercial and non-commercial fruit. The results were submitted to analysis of variance (ANOVA) and, when significant, compared using the Tukey test at a 5% probability of error, using the R program. For the phyllochronum variable, the CAV 1 genotype had a faster vegetative period (106.8 days) and the CAV 2 genotype had a longer vegetative period (165.6 days), but there were no significant differences between the genotypes. Genotype CAV 1 had the shortest vegetative period and CAV 2 the longest, with no significant differences between genotypes. CAV 2 was the earliest at flowering and CAV 8 had the longest time to flowering, with no significant differences at full flowering and the start of harvest. Vernalized seedlings were earlier in all phenological variables except phyllochronum. There were no statistical differences in the number of commercial and non-commercial fruits, nor in the mass of non-commercial fruits. Artificial vernalization did not significantly affect the mass of commercial fruit, except for CAV 2, which had a higher yield without vernalization. It was concluded that artificial vernalization promoted greater precocity in all the genotypes, without significantly affecting phyllochronism, and that seedlings without vernalization resulted in greater fruit production in the CAV 2 genotype, with no significant effect on the other genotypes.
Artificial vernalization in strawberry genotypes
Keywords: Fenologia; Frutos; Precocidade; Produção; Fruit; Phenology; Precocity; Production; CNPQ::CIENCIAS AGRARIAS